Extraction and analysis of plant alkanes and long‐chain alcohols using accelerated solvent extraction (ASE) - Anthony M. Carnahan; Donald E. Spalinger; John M. Kennish; William B. Collins (Wildlife Society Bulletin, 2013)
Abstract We explored a one‐step method of extracting plant cuticular hydrocarbons for the analysis of diet composition, intake, and passage rate of herbivores. Alkanes (waxes produced by plants) and long‐chain alcohols (LCOHs) have traditionally been extracted via a sequence of saponification and esterification (S/E) separation techniques, which are labor‐ and time‐intensive. We improved upon the alkane method by extracting samples in hexane using Dionex's Accelerated Solvent Extractor (ASE®; Dionex Corporation, Bannockburn, IL) with simultaneous purification of long‐chain hydrocarbons using Florisil® (U. S. Silica, Berkeley Springs, WV) and Davisil® (W. R. Grace & Co.‐Conn., Columbia, MD) solid‐phase absorbents. This improvement allows for rapid preparation of samples for analysis of both alkanes and LCOHs for gas chromatography analysis. Recovery and quantification of plant alkanes was assessed using 5 forages that were phenologically and morphologically distinct and endemic to South‐central Alaska, USA, to ensure both methods were tested under conditions for which they would be used. We found that recovery of alkanes was 20% higher (P < 0.0001) for the ASE method compared with the S/E method. Correcting for recovery, we found that both methods provided equivalent estimates of alkane concentrations (r2 = 0.9987). Recovery of LCOHs was significantly higher by 7.8% (P = 0.03) for the ASE method compared with the S/E method. Both methods provided similarly clean extractions, with satisfactory baseline and peak separations. We found that the single‐step ASE process was effective in the extraction, purification, and quantification of both alkanes and LCOHs from plant materials, resulting in significant savings in time while using less corrosive solvents. Recoveries of both alkanes and LCOHs were higher for the ASE method. © 2012 The Wildlife Society.